Histological spectrum and diagnostic challenges in endometrial carcinoma of the uterus - Chandwani, Teena V.; Bhat, Dharitri M.; Deshpande, Archana H. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Endometrial carcinoma is the most common type of malignancy of the uterine corpus accounting for 95% of all primary malignancies. Epidemiological studies have proved the role of unopposed estrogen as an important factor in pathogenesis of endometrial carcinoma. Pathologists play an important role not only in the histological confirmation of the diagnosis, but in subtyping, grading and staging of the tumor. Current study is undertaken to study the histological spectrum in endometrial carcinomas. Methods: Present study includes histologically confirmed cases of endometrial carcinoma of uterine corpus over a period of 24 months (July2020 to June 2022) in a tertiary health care center in central India. After gross examination, and standard sectioning, all these tumors were subtyped on histology and grading, staging was done as per WHO and FIGO recommendations. In cases with diagnostic dispute and overlapping features, IHC markers were applied. Results: Amongst total 30 confirmed cases of endometrial carcinoma, endometrioid type was most common (25) followed by villoglandular and serous type of adenocarcinoma. Architectural and nuclear grading was done in all cases. Staging could be done in hysterectomy specimens only. Difficulties encountered while grading and staging are discussed. Conclusions: Endometrial carcinoma was the most common type of malignancy. Other types were villoglandular and serous adenocarcinoma. Various additional histological features were also observed. Grade I tumors were commonly seen. Depth of myometrial invasion was measured in hysterectomy specimens. Various diagnostic challenges encountered are discussed.